"Competence" and occupational standards: observations from six European countries. Issue 2 (13th February 2017) - Lester, Stan; Religa, Jolanta
Abstract : Purpose: The purpose of this paper is to review the use of "competence" as a concept and through the use of occupational competence standards in six European countries. Design/methodology/approach: Partners in an Erasmus+ project in each of the six countries prepared a review of the use of "competence" in their countries using a common template. The authors of this paper reviewed additional literature, summarised the individual country reviews and provided an analysis and commentary. Findings: "Competence" is becoming a widely used concept across Europe, but its interpretation and application both vary. Between them, the countries in the study illustrate the use of separate occupational standards, both as a national strategy and developed by self-governing professions; as well as competence embedded directly in qualification and training specifications. The use of separate standards as a mandatory component in national vocational education and training systems is questioned, while the use of appropriate standards for licensing and qualified status is largely endorsed. Research limitations/implications: The country reviews were conducted principally from the perspective of informing the developments taking place in the project, so were not comprehensive and also differed in emphasis between countries. Practical implications: The study points to the need to avoid promoting any particular model of occupational competence at a European level, as opposed to seeking common ground that will aid mutual recognition of qualifications. It also cautions against the uncritical transfer of models and policies from one national system to another. Originality/value: The paper provides additional evidence against "policy borrowing" without careful consideration of context, and contrasts the use of competence standards as part of a system-wide strategy with their tailored application for specific purposes.